A new low-molecular-weight component promoting adrenergic development in cultured chick sympathetic neurons - Zurn, AD (J Neurosci, 1987)
A low-molecular-weight component present in medium conditioned by cultured chick liver cells (LCM) enhances the adrenergic properties of dissociated chick superior cervical ganglion (SCG) neurons in culture (Zurn and Mudry, 1986). This substance cannot replace NGF as a survival, growth, or differentiation factor. However, in the presence of NGF, it stimulates neuronal metabolism and catecholamine (CA), but not ACh production by the SCG neurons. The effect on transmitter production is greater than that on neuronal metabolism. Yet this is not due to an increase in the specific activity of tyrosine hydroxylase (TH), the rate-limiting enzyme in CA synthesis. Interestingly, the effect of LCM on CA and ACh production, but not on neuronal metabolism, is potentiated in the presence of a large excess of NGF. The active component(s) present in LCM has a molecular weight lower than 500 Da and is not inactivated by heat or pronase treatment. So far, none of the small molecules tested (ascorbic acid, pyruvate, glucose, L- glutamic acid, glutathione, etc.) were able to mimic the effects of LCM on the SCG neurons. Thus this report describes a novel low-molecular- weight component different from NGF that promotes metabolism and adrenergic development in cultured chick sympathetic neurons.